A role for Quox-8 in the establishment of the dorsoventral pattern during vertebrate development. - Takahashi, Y (1992)
We have been interested in the possible involvement of the gene Quox-8, a member of the Hox-7/msh family of homeobox-containing genes in the patterning of the neural tube and the somitic-derived mesoderm. We demonstrate that in the embryonic day 2-6 avian embryo, the expression of Quox-8 in the roof plate depends upon (i) the normal dorsoventral orientation of the neural primordium and (ii) interactions between the dorsal neural tube and the superficial ectoderm. We also show that Quox-8 is expressed in the dorsal mesenchyme located between the neural tube and the superficial ectoderm that yields the spinous processes of the vertebrae. Experimental inhibition of Quox-8 expression in these areas of the dorsal mesenchyme results in the failure of its differentiation into vertebral cartilage. We conclude, therefore, that this gene is involved in the patterning of vertebral structures through a cascade of tissue interactions primarily occurring between the dorsal neural tube and the overlying ectoderm.